Navigating the Future of Sustainable Food Tourism : Implications for Marketers, Policymakers, and Researchers - Ravichandran, Sabari Shankar (Prabandhan: Indian Journal of Management, 2025)
Purpose : This research note was an extract from primary research on sustainable food tourists’ behaviours. Evolving tourist behaviours, stakeholder dynamics, the need for sustainability focus, and digital mediation that regulate sustainable food tourism competitiveness were the driving forces. This study proposed an integrated agenda for research, marketing, and policymaking that reflected the evolving complexity of sustainable food consumption in tourism. Methods : This note was produced based on the three dimensions — theoretical background, insights from Focus Group Discussion, and analysis of the other secondary non-academic sources. The implications were generated by integrating the theoretical frameworks, including cultural capital theory, stakeholder theory, self-determination theory, and affordance theory, insights from focus group discussions (FGDs) conducted with 12 food retailers across diverse destinations, and secondary analysis of existing research on social media influence, technological affordances, and sustainable lifestyle values. Significant Findings : Visitors sought authentic, ethical food-related experiences tied to values of sustainability, albeit with small producers being marginalized through power asymmetries. Digital media framed understanding but re-reflected inequalities of access across race, class, and gender. Novelty : The research transcended fixed consumer models by demonstrating sustainable food tourism as dynamic, relational, and mediated by technology and identity intersections, providing a critical rethinking of theorizing tourist behaviours. Implications : Researchers, policymakers, and marketers must ensure digital inclusion, empower local producers, certify authenticity, and harmonize efforts with SDG 12 to create resilient, equitable, and sustainable food tourism systems.